Žiznʹ i smertʹ v kruženʹe večnom: O metamorfozach czasu w twórczości Aleksandra Błoka .......... 479 - Malej, Izabella (Czas w kulturze rosyjskiej, 2019)
“ЖИЗНЬ И СМЕРТЬ В КРУЖЕНЬЕ ВЕЧНОМ”. ABOUT METAMORPHOSES OF TIME IN THE WORKS OF ALEXANDER BLOKIn the works of Alexander Blok, especially in the initial phase (Ante Lucem [1898-1900]; Verses about the Beautiful Lady [1901-1902]; Crossroads [1902-1904]; Timelessness [1906]), its presence clearly marks the time as the element of transformation, taking various figural forms. The most important of the time modes of the Russian symbolist is the circular time, which contains the memory of both the Platonic idea of time – a dynamic copy of eternity and the concept of the eternal return of Friedrich Nietzsche. Thus, in the poetic narrative of Blok, there is a discourse between the power of will and the power of eternity, whereas time becomes the wheel in the mystical act after many experienced affirmations. The poet does not understand the eternal return as a negation of time, though he would like to keep it sometimes, or as a timeless eternity. On the contrary, eternity and time function as inseparable unity for Blok.